2020
DOI: 10.51791/njap.v46i4.296
|View full text |Cite
|
Sign up to set email alerts
|

Kaempferol improved growth performance in broiler chickens challenged with Eimeria tenella

Abstract: The study investigated the effects of kaempferol on growth performance in two weeks old broilers challenged with Eimeria tenella. Sixty, one-day old broiler chicks were randomly allotted into six groups (I-VI) of ten broiler chicks each and brooded for two weeks with commercial broiler feed (vital feed®) and provided water ad libitum. At two weeks of age, broilers in group 1 were neither infected nor treated. Broilers in groups II- VI were infected 4 with Eimeria tenella sporulated oocyst (10 /mL) via oral ino… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
0
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(1 citation statement)
references
References 0 publications
1
0
0
Order By: Relevance
“…The hematological results of this study indicated macrocytic hypochromic anemia in the birds infected with E. tenella at the 21st and 28th days of the experiment evidenced by significantly decreases in RBCs, Hb, PCV%, and MCHC values and significantly increases in MCV values. These results agree with Youssef et al (2015).Histamine is generated during tissue injury induced by E. tenella, increasing the permeability of blood capillaries and venules, which allows for the escaping of significant amounts of blood, which could be the cause of anemia (Muhammad et al, 2020). In comparison to the infected group, the diclazuril-treated group showed a significantly higher Hb concentration, PCV%, and RBC count as well as significantly higher MCV values.…”
Section: Discussionsupporting
confidence: 91%
“…The hematological results of this study indicated macrocytic hypochromic anemia in the birds infected with E. tenella at the 21st and 28th days of the experiment evidenced by significantly decreases in RBCs, Hb, PCV%, and MCHC values and significantly increases in MCV values. These results agree with Youssef et al (2015).Histamine is generated during tissue injury induced by E. tenella, increasing the permeability of blood capillaries and venules, which allows for the escaping of significant amounts of blood, which could be the cause of anemia (Muhammad et al, 2020). In comparison to the infected group, the diclazuril-treated group showed a significantly higher Hb concentration, PCV%, and RBC count as well as significantly higher MCV values.…”
Section: Discussionsupporting
confidence: 91%